CARA MEMPERKECIL BIAYA LANGGANAN DAYA KE PLN DAN MENGEFISIENKAN PEMAKAIAN DAYA LISTRIK KEBUTUHAN RUMAH TANGGA - Lugito, Dharmananda (Jurnal Teknik Elektro, 2001)
Nowadays the electric energy cost is always increasing every year. So we need to save inusing electric energy. To increase electric efficiency some efforts can be done, for exampleby reducing the load harmonic, increasing power factor (cos ï¦) and minimizing the startingcurrent of electrical machine; so we only buy electric energy that we need really to be used,or for only active load that we need in our home. For this occasion we discuss only forsmall load as many usages in living home, but it indeed can be continued for larger load ashigh rise buildings, industries, factories, etc.Keywords: Power factor, harmonic distortion, electrical machine